Random tensors - Gurǎu, Rǎzvan (Oxford University Press, 2017)
Written by the creator of the modern theory of random tensors, this is a self-contained introductory text to this rapidly developing theory. Starting from notions familiar to the average researcher or PhD student in mathematical or theoretical physics, it presents in detail the theory and its applications to physics.
This edition previously issued in print: 2016. - Includes bibliographical references and index. - Description based on online resource; title from home page (viewed on December 7, 2016)
Keywords: Graphentheorie; Tensor; Stochastische Geometrie